Life expectancy and disparities in survival among HIV-infected people receiving antiretroviral therapy: an observational cohort study in Kathmandu, Nepal - Dharma N Bhatta; Ruchi Adhikari; Sushil Karki; Arun K Koirala; Sharada P Wasti (BMJ Global Health)
Introduction The advent of antiretroviral therapy (ART) has dramatically slowed down the progression of HIV. This study assesses the disparities in survival, life expectancy and determinants of survival among HIV-infected people receiving ART.Methods Using data from one of Nepal’s largest population-based retrospective cohort studies (in Kathmandu, Nepal), we followed a total of 3191 HIV-infected people aged 15 years and older who received ART over the period of 2004–2015. We created abridged life tables with age-specific survival rates and life expectancy, stratified by sex, ethnicity, CD4 cell counts and the WHO-classified clinical stage at initiation of ART.Results HIV-infected people who initiated ART with a CD4 cell count of >200 cells/cm3 at 15 years had 27.4 (22.3 to 32.6) years of additional life. People at WHO-classified clinical stage I and 15 years of age who initiated ART had 23.1 (16.6 to 29.7) years of additional life. Life expectancy increased alongside the CD4 cell count and decreased as clinical stages progressed upward. The study cohort contributed 8484.8 person years, with an overall survival rate of 3.3 per 100 person years (95% CI 3.0 to 3.7).Conclusions There are disparities in survival among HIV-infected people in Nepal. The survival payback of ART is proven; however, late diagnosis or the health system as a whole will affect the control and treatment of the illness. This study offers evidence of the benefits of enrolling early in care in general and ART in particular.